An overview of precast concrete system for building maintenance: Malaysian perspective - Ng, Ban Kiong; Akasah, Zainal Abidin (2012)
Precast Concrete System which is mass produced either in factory or at site factory is widely used as building components. The components are usually designed according to the specified standard shapes and dimensions. The components will then be transported to the construction site to be placed according to the building design requirements. Previous studies indicate that without proper planning at the design, manufacturing and construction stages of the precast system, the use of precast concrete system often leads to building maintenance issues. This paper will discuss the factors that will lead to maintenance issues for building using precast concrete system. These factors will be those that need to be considered at the design, manufacturing and construction stage for the precast concrete system. Lastly, recommendations are proposed to be used by designers, contractors, manufacturers and researchers who are involved in precast concrete system.